Opposing functions of H2BK120 ubiquitylation and H3K79 methylation in the regulation of pluripotency by the Paf1 complex. Issue 24 (17th December 2017) - Strikoudis, Alexandros; Lazaris, Charalampos; Ntziachristos, Panagiotis; Tsirigos, Aristotelis; Aifantis, Iannis
ABSTRACT: Maintenance of stem cell plasticity is determined by the ability to balance opposing forces that control gene expression. Regulation of transcriptional networks, signaling cues and chromatin-modifying mechanisms constitute crucial determinants of tissue equilibrium. Histone modifications can affect chromatin compaction, therefore co-transcriptional events that influence their deposition determine the propensities toward quiescence, self-renewal, or cell specification. The Paf1 complex (Paf1C) is a critical regulator of RNA PolII elongation that controls gene expression and deposition of histone modifications, however few studies have focused on its role affecting stem cell fate decisions. Here we delineate the functions of Paf1C in pluripotency and characterize its impact in deposition of H2B ubiquitylation (H2BK120-ub) and H3K79 methylation (H3K79me), 2 fundamental histone marks that shape transcriptional regulation. We identify that H2BK120-ub is increased in the absence of Paf1C on its embryonic stem cell targets, in sharp contrast to H3K79me, suggesting opposite functions in the maintenance of self-renewal. Furthermore, we found that core pluripotency genes are characterized by a dual gain of H2BK120-ub and loss of H3K79me on their gene bodies. Our findings elucidate molecular mechanisms of cellular adaptation and reveal novel functions of Paf1C in the regulation of the self-renewal network.